2017
DOI: 10.1097/md.0000000000006766
|View full text |Cite
|
Sign up to set email alerts
|

Isolated olecranon fractures in children affected by osteogenesis imperfecta type I treated with single screw or tension band wiring system

Abstract: The purpose of this study is to compare the results of 2 techniques, tension band wiring (TBW) and fixation with screws, in olecranon fractures in children affected with osteogenesis imperfecta (OI) type I. Between 2010 and 2014, 21 olecranon fractures in 18 children with OI (average age: 12 years old) were treated surgically. Ten patients were treated with the screw fixation and 11 with TBW. A total of 65% of olecranon fractures occurred as a result of a spontaneous avulsion of the olecranon during the contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 31 publications
4
29
0
Order By: Relevance
“…Previous literature has established that patients with OI tend to sustain olecranon fractures under low-energy mechanisms 4–7,12. Our study supports these findings and we report a significant difference in mechanism of injury between OI and non-OI patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous literature has established that patients with OI tend to sustain olecranon fractures under low-energy mechanisms 4–7,12. Our study supports these findings and we report a significant difference in mechanism of injury between OI and non-OI patients.…”
Section: Discussionsupporting
confidence: 91%
“…OI patients were treated more frequently with ORIF using TBW as this method has been shown to shorten immobilization and recovery time. 12 When patients are initially diagnosed with OI, they should be counseled on their higher likelihood for surgery following a fracture, particularly of the olecranon.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there is no difference in the reoperation and complication rates between TBW and screw xation in adult olecranon fracture [18]. However, it should be noted that in patients with OI type I, there is a risk of loose internal xation, which can be attributed to an inadequate adhesion of the implant to the osteoporotic bone in these patients [12]. In our study, the elbow joint was straightened and exed after the Herbert screws were implanted to assess the stability of the cannulated screws.…”
Section: Discussionmentioning
confidence: 95%
“…Persiani et al reported the outcomes of treatment of olecranon fractures in children affected with osteogenesis imperfecta (OI) type I by screw xation. Although screws provided good xation, there was a high risk for implant migration; dispalcement of the internal xation device occurred in the three of the 10 patients [12]. However, limited studies have reported on the use of screws for isolated olecranon fractures in healthy children and skeletally immature patients.…”
Section: Introductionmentioning
confidence: 99%
“…They typically occur following a direct blow to the olecranon or a fall onto a flexed elbow. Children with osteogenesis imperfecta (OI) have an increased incidence of this injury and a high incidence of bilateral asynchronous olecranon fractures [ 1 , 2 ]. This injury is more commonly seen in type 1 OI, compared to other more severe forms of the condition [ 2 - 5 ].…”
Section: Introductionmentioning
confidence: 99%